Keadilan Gender: (Analisis Tentang Peran Publik Perempuan Dari Aspek Tradisi Budaya, Konstruksi Sosial dan Demokrasi) - Shofiyah, Shofiyah (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2016)
During this time women are seen as a weak creature, but men are assumed as a greater human figure, more intelligent and intellectual than women, so women are considered unworthy and unfit to be a leader. Yet Islam itself upholds the dignity of women and even the Qur'an recognizes the leadership of Queen Bilqis. From the time of the Messenger of Allah to the many real figures of women who managed to become leaders, but its existence seemed regarded as nothing, this is due to the male domination of the more prominent, so in fiqhpun as if many who mendiskriditkan women. That's why it needs to be examined and examined its truth, until it can prove that the fiqh rules about women really need a renewal as a form of answer from the development of the times.